Assessing COVID-19 cohorting strategies in a UK district general hospital during the first wave of COVID-19. (2021) - Davies, Tim; Cargill, Tamsin; Shaw, Robert; Ellis, Tony; Jeffery, Katie; Wangrangsimakul, Tri
No abstract available